Preconception Substance Use and Risk of Unintended Pregnancy: Pregnancy Risk Assessment Monitoring System 2016–17. Issue 3 (May 2022) - Shafique, Saima; Umer, Amna; Innes, Kim E.; Rudisill, Toni Marie; Fang, Wei; Cottrell, Lesley
Abstract : Objective: This study examined the association between preconception substance use and unintended pregnancy in a large, nationally representative sample of women. Methods: In this cross-sectional study, we used data from the Pregnancy Risk Assessment Monitoring System (PRAMS) comprising, 74, 543women who had birth during 2016–17. Logistic regression was used to assess the independent association of unintended pregnancy overall and by subtypes to preconception substance use (smoking and other nicotine/tobacco use, alcohol consumption, and use of cannabis, illicit/recreational drugs) and specific medication including prescription opioids, antidepressants and over the counter pain relief. Results: Overall, 41% of pregnancies were unintended. Nearly 57% of participants reported alcohol consumption during the preconception period, with 32% indicating binge drinking, 17% reported preconception smoking, and 10% cannabis use. Unintended pregnancy was significantly associated with substance use, including smoking (adjusted odds ratio [AOR]:1.5, 95% confidence interval [CI]: 1.4–1.6); as well as the use of other nicotine/tobacco (AOR:1.4, 95% CI: 1.3–1.5); cannabis (AOR: 1.9, 95% CI: 1.5–2.3); illicit/recreational drugs (AOR:1.7, 95% CI: 1.2–2.4), prescription opioids (AOR:1.4, 95% CI: 1.02–1.9), and prescription antidepressants (AOR 1.8, 95% CI: 1.1–3.0). The likelihood of unintended pregnancy was significantly elevated with heavy smoking, heavy alcohol consumption, and binge drinking. Analyses by unintended pregnancy subtype yielded similar results. Conclusions: Preconception substance use was significantly and positively associated with unintended pregnancy. Evidence-based interventions are needed addressing substance use behavior and effective contraceptive use to prevent unintended pregnancy and related adverse effects on maternal and child health.